Предмет: Математика,
автор: Kosha99
(1|√ 7-√ 6)-(3|√ 6-√ 3)-(4|√ 7+√ 3)
Ответы
Автор ответа:
0
(√7+√6)/(√7-√6)(√7+√6) -3(√6+√3)/(√6-√3)(√6+√3) -4(√7-√3)/(√7+√3)(√7-√3)=
=(√7+√6)/1 -3(√6+√3)/3-4(√7-√3)/4=√7+√6-√6-√3-√7+√3=0
=(√7+√6)/1 -3(√6+√3)/3-4(√7-√3)/4=√7+√6-√6-√3-√7+√3=0
Автор ответа:
0
Спасибо!
Похожие вопросы
Предмет: География,
автор: kindermister10
Предмет: Математика,
автор: beisenersin09
Предмет: Физика,
автор: 1timuribra
Предмет: Геометрия,
автор: Кариночка200125
Предмет: Алгебра,
автор: Александр4441